Democracy struggles : NGOs and the politics of aid in Serbia - Vetta, Theodora (Dislocations, 2018)
Tracing the boom of local NGOs since the 1990s in the context of the global political economy of aid, current trends of neoliberal state restructuring, and shifting post-Cold War hegemonies, this book explores the 'associational revolution' in post-socialist, post-conflict Serbia. Looking into the country's 'transition' through a global and relational analytical prism, the ethnography unpacks the various forms of dispossession and inequality entailed in the democracy-promotion project.